Storability, longevity and rancidity: A genomic perspective on evolutionary constraints in major oilseeds: Storability, longevity and rancidity: A genomic perspective on evolutionary constraints in major oilseeds - RAMYA PARAKKUNNEL; BHOJARAJA NAIK K; GIRIMALLA VANISHREE; KT RAMYA; ANJITHA GEORGE; KV SRIPATHY; CS SHANTHARAJA; S ARAVINDAN; K UDAYA BHASKAR; A ANANDAN; SANJAY KUMAR (Journal of Oilseeds Research, 2023)
Limited longevity and accelerated chemical decomposition during storage are major problems found in oilseeds. In the present study the genomic composition of rancidity prone soybean and sunflower are compared with oil seeds with fairly good storability like sesame and olive. The chromosomal location, gene duplications, syntenic relationships, cis-element architecture and protein-protein interactions were studied with respect to 250 genes affecting lipid decomposition like lipases, lipoxygenases and oleosins. The expansion of lipoxygenases and phospholipaseD genes in soybean and sunflower indicate the importance of gene duplication in functional divergence. Moreover the effect of strong purifying selection in lipid decomposition genes was evident in shaping the genomic diversity.